Cyberbullying and internet safety: a survey of child and adolescent mental health practitioners. (28th March 2023) - Lonergan, Aoife; Moriarty, Amy; McNicholas, Fiona; Byrne, Triona
Abstract : Objectives: Cyberbullying is increasingly recognised as a threat for young people's mental health. Young people and their families may not know how to stay safe online or how to respond following unsafe internet experiences. This study aimed to examine Child and Adolescent Mental Health Service (CAMHS) staff perceived knowledge, practice and attitudes towards cyberbullying (CB) and internet safety (IS), and their training needs. Methods: A descriptive, survey design was used. 59 CAMHS clinicians completed a study specific online survey examining their knowledge, practice, attitudes and training needs regarding CB and IS. Frequency and descriptive statistics were conducted on participant responses. Results: Clinicians reported that risky internet behaviour and CB were frequent experiences reported by youth attending their clinical practice. Professionals were aware of potential adverse effects on the young person, including social withdrawal, low self-esteem, anxiety, self-injurious behaviour and suicidal thoughts. Training for young people on online behaviour and good digital citizenship skills was a highly endorsed preference. The majority of respondents felt CAMHS staff have a role in supporting families and managing IS and identified training and resource materials as strategies to assist them in this regard. Conclusions: Findings support a need for clinicians to regularly inquire about internet use, safety and adverse online experiences. The ongoing development of resources and training in CB and IS for CAMHS clinicians, children and caregivers is necessary. Further research is warranted due to the small sample size and the subjective nature of the current study.